Utilization of e-learning platforms by lecturers during the COVID-19 pandemic in Indonesia - Dian Tauhidah; Ummi Nur Afinni Dwi Jayanti; Amining Rahmasiwi; Rahmania Pamungkas; Ahmad Saifulloh (JPBI (Jurnal Pendidikan Biologi Indonesia), 2021)
The current COVID-19 pandemic forces the educational field to adapt to e-learning to continue teaching and learning. This study aimed to analyze the use of e-learning platforms during the COVID-19 crisis, especially in the biology education program. This study used a quantitative survey design. Through purposive sampling, 100 lecturers from 43 universities in Indonesia participated in this study. Data collection was carried out by using an online questionnaire. Data were analyzed using descriptive statistics and thematic content analysis. The findings showed that WhatsApp, Google Classroom, and Zoom remain the most used e-learning platforms in Indonesian universities due to their accessibility and affordability. Participants’ obstacles during online learning centered on the limited network and quota as well as controlling aspects. Suggestions for further online learning are providing internet quota assistance, infrastructure, and network refinement and planning a comprehensive and careful learning design. The findings of this study can be a reference for biology education lecturers as well as universities officials in determining and using e-learning platforms during COVID-19 to improve online learning in Indonesian higher education during the pandemic.